Hubungan Pola Kuman Saluran Cerna Anak Autis terhadap Tumbuh Kembang di Kota Jambi - Putra, Irawan Anasta; Syauqy, Ahmad (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background: Autism is developmental disorder that appears in children before the age of three and the cause is not known yet. Characteristics of autism are deficits in communication, social interaction, behavior and indigestion. Therapy for autism is not only behavioural therapy but also gluten free-casein free diet. The aim of this study is to describe the characteristics of the growth and development of children with autism at the age of 2-6 years and to see the possibility of the relationship between the pattern of microbe in tractus gastrointestinal and the growth level in children. Methods: Descriptive cross-sectional study, included 49 children with autism at the age of 2-6 years and their parents in special schools of Prof. Dr. Sri Soedewi Masjchun Sofwan, SH and three foundation of children with special needs in Jambi city. Result: 89,8% respondents aged 4-6 years; 87,9% dominated by boys; 87,8% autism is more common in pregnant women aged 21-35 years; 61,2% mothers had never experienced TORCH infection; 93,9% gave birth at >37-42 weeks gestation; 85,7% respondents had never experienced signs of severe breathing at birth; 89,8% had never experienced signs of meningitis or seizures; 33 parents have known about GFCF diet, but only 28 parents who apply the diet. From 28 parents; 21 replace cow’s milk to soy milk, 12 regular and discipline on the diet and 20 felts the positive effects of the diets. 49 respondents: 69,4% has normal nutritional status and 98% has suspect in development disorders. There are the relationships in statistic between the growth level of autism child with microbe Proteus mirabilis. Conclusion: The majority of children with autism at the age of 2-6 years in Jambi City have normal growth, yet fall into the category of suspect in developmental disorders. Proteus mirabilis is a microbe which has the relationships statistically with the growth level of autism children. Keywords: Autism, growth, development, pattern of microbe